Inpatient burden of childhood functional GI disorders in the USA: an analysis of national trends in the USA from 1997 to 2009. Issue 5 (22nd March 2015) - Park, R.; Mikami, S.; LeClair, J.; Bollom, A.; Lembo, C.; Sethi, S.; Lembo, A.; Jones, M.; Cheng, V.; Friedlander, E.; Nurko, S.
Abstract: Background: Functional gastrointestinal disorders (FGIDs) are among the most common outpatient diagnoses in pediatric primary care and gastroenterology. There is limited data on the inpatient burden of childhood FGIDs in the USA. The aim of this study was to evaluate the inpatient admission rate, length of stay (LoS), and associated costs related to FGIDs from 1997 to 2009. Methods: We analyzed the Kids' Inpatient Sample Database (KID) for all subjects in which constipation (ICD‐9 codes: 564.0–564.09), abdominal pain (ICD‐9 codes: 789.0–789.09), irritable bowel syndrome (IBS) (ICD‐9 code: 564.1), abdominal migraine (ICD‐9 code: 346.80 and 346.81) dyspepsia (ICD‐9 code: 536.8), or fecal incontinence (ICD‐codes: 787.6–787.63) was the primary discharge diagnosis from 1997 to 2009. The KID is the largest publicly available all‐payer inpatient database in the USA, containing data from 2 to 3 million pediatric hospital stays yearly. Key Results: From 1997 to 2009, the number of discharges with a FGID primary diagnosis increased slightly from 6 348 537 to 6 393 803. The total mean cost per discharge increased significantly from $6115 to $18 058 despite the LoS remaining relatively stable. Constipation and abdominal pain were the most common FGID discharge diagnoses. Abdominal pain and abdominal migraine discharges were most frequent in the 10–14 year age group. Constipation and fecal incontinence discharges were most frequent in the 5–9 year age group. IBS discharge was most common for the 15–17 year age group. Conclusions & Inferences: Hospitalizations and associated costs in childhood FGIDs have increased in number and cost in the USA from 1997 to 2009. Further studies to determine optimal methods to avoid unnecessary hospitalizations and potentially harmful diagnostic testing are indicated. Abstract : The aim of this study was to evaluate the inpatient admission rate, length of stay, and associated costs related to FGIDs from 1997 to 2009. We analyzed the Kids' Inpatient Sample Database for which constipation, abdominal pain, irritable bowel syndrome, abdominal migraine, dyspepsia, or fecal incontinence was the primary discharge diagnosis. We found that hospitalizations and associated costs in childhood FGIDs have increased in number and cost in the USA from 1997 to 2009.